Manfred Winklers Poetologie der Inspiration - Schrader, Hans-Jürgen (Naharaim, 2025)
Throughout his life, Manfred Winkler thought restlessly about the impulses for his poems (as well as for his clay statuettes). In his Celan essay, in countless letters, and often in his poems themselves, he tried to give an account of the extent to which his artistic activity was the result of an inner calling, an unconscious creative urge that could hardly be controlled rationally, while it still remained subject to his own will, a certain intention of expression and form. For Winkler, an inspirational impulse, an indeterminate mood, bars of music, or the rhythms of verses, words, or phrases, seemed to be more essential to his art than calculated messages or technical and formal refinement. Even though he spoke of these inspirations in an unpretentious, sobering way, his approach could be characterized as a pre-classical, and later also impressionistic, concept of poetry.